Patients Awaiting Surgical Repair for Large Abdominal Aortic Aneurysms Can Exercise at Moderate to Hard Intensities with a Low Risk of Adverse Events - Weston, Matthew; Batterham, Alan M.; Tew, Garry A.; Kothmann, Elke; Kerr, Karen; Nawaz, Shah; Yates, David; Danjoux, Gerard (Frontiers in Physiology, 2017)
Purpose: Intervention fidelity refers to the extent an experimental manipulation has been implemented as intended. Our aim was to evaluate the fidelity high-intensity interval training (HIT) in patients awaiting repair of large abdominal aortic aneurysms. Methods: Following a baseline cardiopulmonary exercise test, 27 participants performed a hospital-based, supervised HIT intervention in the four weeks preceding surgery. The intervention was performed thrice weekly on a cycle ergometer and involved either 8 × 2-min intervals, each interspersed by 2-min recovery periods, or 4 × 4-min intervals interspersed with 4-min recovery periods. When surgery was delayed, participants undertook one maintenance HIT session per week until surgery. Session one power output was set to baseline anaerobic threshold power output and then increased on subsequent sessions until ratings of perceived exertion (RPE; Borg CR-10) for the legs (RPE-L) and sense of breathlessness/ chest (RPE-C) were hard (5) to very hard (7) at the end of each interval. For safety, power output was maintained or reduced if systolic blood pressure exceeded 180 mm Hg or heart rate exceeded 95% of maximum. Results: Overall session attendance across the 4-week HIT intervention was 74%. Seventeen participants met our compliance criteria of ≥75% of intervention sessions and all maintenance sessions. When compared to non-compliance, compliant participants had higher fitness, performed more HIT sessions and were able to exercise at higher exercise intensities with a lower proportion of exercise safety breaches. In the 17 compliant participants, the proportion of repetitions meeting the HIT criterion was 30% (RPE-L) and 16% (RPE-C). Mean repetition intensity was 4.1 ± 2.0 Arbitrary Units [AU] (RPE-L) and 3.5 ± 1.9 AU (RPE-C) with a within-subject variability of ±1.4 AU and ±1.6 AU, respectively. We observed higher RPE scores (~0.5 AU) following 2-min intervals when compared to 4-min intervals and exercise power output increased 23% across the 4-week HIT intervention. One participant experienced an adverse event but were still able to complete their remaining exercise sessions. Conclusions: Despite an inconsistent and lower than prescribed intensity, it is possible to exercise this high-risk patient population at moderate to hard intensities with a low risk of adverse events.